Revascularization of AlloDerm Used during Endoscopic Skull Base Surgery - Taufique, Zahrah M.; Bhatt, Nupur; Zagzag, David; Lebowitz, Richard A.; Lieberman, Seth M. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives AlloDerm is an acellular dermal matrix often used for reconstruction throughout the body. AlloDerm has been shown to undergo revascularization when used to reconstruct soft tissue such as in abdominal wall reconstruction. In this study, the authors review the literature on revascularization of AlloDerm and demonstrate the histologic findings of AlloDerm after implantation during skull base reconstruction.Study Design Literature review and case reports.Setting Tertiary Care InstitutionParticipants Patients from a tertiary care institutionMain Outcome Measures Histologic slides are evaluated and compared with nonimplanted AlloDerm.Methods The authors review a case of explanted AlloDerm that had been used for skull base reconstruction after endoscopic skull base surgery.Results Upon reviewing the histologic slides of explanted AlloDerm to nonimplanted AlloDerm, we demonstrate revascularization of AlloDerm when used in skull base reconstruction. Representative slides will be included.Conclusions AlloDerm undergoes revascularization when used for skull base reconstruction.
Keywords: AlloDerm; skull base surgery; skull base reconstruction; acellular dermal matrix; revascularization